2004
DOI: 10.1136/gut.2003.017442
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localisation of matrix metalloproteinases and their natural inhibitors in fistulae of patients with Crohn's disease

Abstract: Background: Fistulae are a troublesome complication of Crohn's disease but little is known of the final effector molecules responsible for matrix degradation. Although matrix metalloproteinases (MMPs) have been strongly implicated in tissue injury in Crohn's disease, their role in fistula formation is unknown. Aim: To determine the expression pattern of MMPs and tissue inhibitors of metalloproteinases (TIMPs) in fistulae of patients with Crohn's disease. Patients and methods: Resected fistula specimens were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
172
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 35 publications
6
172
3
6
Order By: Relevance
“…The best characterized function of CD147 is production and activation of matrix-metalloproteases (MMPs) and involvement in cell adhesion (Choi et al, 2002;Lim et al, 1998;Schmidt et al, 2006). Remarkably, patients suffering from Crohn disease show enhanced expression levels of MMP1 and MMP9 in colonic tissue, especially in fistulae (Kirkegaard et al, 2004;Stumpf et al, 2005). Further studies will have to clarify if CD147 directly contributes to MMP dysregulation in chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The best characterized function of CD147 is production and activation of matrix-metalloproteases (MMPs) and involvement in cell adhesion (Choi et al, 2002;Lim et al, 1998;Schmidt et al, 2006). Remarkably, patients suffering from Crohn disease show enhanced expression levels of MMP1 and MMP9 in colonic tissue, especially in fistulae (Kirkegaard et al, 2004;Stumpf et al, 2005). Further studies will have to clarify if CD147 directly contributes to MMP dysregulation in chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors further showed that fibroblast-derived MMP-2 was required for stromal remodeling that is integral to corneal wound healing. Along with the observations that myofibroblasts are an important source of MMP-2 during intestinal inflammation (19) and are integral to epithelial wound healing, it is likely that MMP-2 may play a role in tissue remodeling that is required for proper wound healing (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Although MMPs play important roles in normal tissue remodeling, dysregulated expression has been implicated in several pathological processes, such as arthritis (1,12), atherosclerosis, myocardial infarction (13), colorectal cancer, tumor invasion (14,15), and IBD (4,16). In many acute and chronic inflammatory events such as IBD, MMP levels have been shown to be up-regulated (17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Furthermore, we demonstrated that pro-MMP-1 is not directly activated by mature CP-A5; in fact, CP-A5 activates pro-MMP-3, which in turn activates pro-MMP-1. Stromelysin-1 (MMP-3) cleaves proteoglycans, collagen (types II, IX and XI), gelatin, laminin and fibronectin, and has been linked to tissue degradation in pathological situations (such as inflammatory bowel disease and Crohn's disease) in which MMP-3 contributes to ECM degradation 28,29 . In our disease model, MMP-3 was expressed by epithelial cells, suggesting that this enzyme could contribute to extensive desquamation through degradation of the basal membrane, which supports the epithelial cells lining in the colon.…”
Section: Discussionmentioning
confidence: 99%